Distinguishing Organisational Profiles of Food Loss Management in Logistics - Julia Kleineidam (Logistics)
Background: Food loss management (FLM), which is discussed at length in the literature, lacks a scientific basis on which to determine the current engagement of actors in the food value chain and what is relevant to derive appropriate measures according to the circumstances in the organisations concerned. Therefore, this paper aims to derive patterns by which the engagement of actors can be distinguished and, on this basis, to make recommendations for further action. Methods: Based on an online survey of 40 participants, a clustering analysis was conducted using the unsupervised learning method and hierarchical clustering (R and R Studio). Results: Five clusters representing different profiles were derived, showing how actors in the food value chain have addressed FLM in the past. The derived profiles do not represent stages of development but rather characteristics of organisations that have addressed FLM in a certain way in the past. Conclusions: For the five organisational profiles, recommendations for action were given for further engagement with FLM. As the level of engagement with FLM increases, organisations should tackle increasingly complex measures to reduce food losses. At the same time, a shift in measures from the tactical to the strategic planning level was derived.